Home is Where the Habit of the Heart is: Governing a gendered sphere of belonging. (3rd May 2016) - de Wilde, Mandy
Abstract: Dutch neighborhood policy is increasingly, and quite literally, addressing the habits of the heart—residents' values, emotions, and intimate relationships—to encourage what we may call "affective citizenship." Central to this governmental strategy is the creation of communities as spheres of belonging. This article focuses on neighborhoods as potential spaces of belonging and the role that "feeling at home" plays in residents' community participation. More specifically, the article focuses on how immigrant women who are subject to the policy interventionism of a community participation program make use of a neighborhood center—a "parochial space"—in a Dutch urban neighborhood. I show how the program resonates with and affects their feelings of home; and, I address how the practices, concerns, and emotions of an intimate, gendered, domestic sphere are given expression in "parochial spaces" through the encounters and activities of immigrant women, thereby blurring the boundaries between what is conventionally considered public and private. Also, I show how this enacts a gendered sphere of belonging that enables women to cultivate bonds of affinity with other women in the neighborhood. I argue that the governmental strategy of "affective citizenship" allows immigrant women to express their emotions, values, and morals through domesticating space, feminizing culture, and "whispering voice." Despite the feelings of belonging experienced by many immigrant women, the case study reveals how this does not lead to an inclusive community but often to a community that is fragile, temporary, and exclusive. The article thereby reveals the dynamism of belonging and why it is so difficult to plan and manage for the benefit of community building.